OP0180 TLR4 and VEGF polymorphisms in chronic periaortitis. (23rd January 2014) - Atzeni, F.; Boiardi, L.; Vaglio, A.; Nicoli, D.; Farnetti, E.; Palmisano, A.; Pipitone, N.; Casali, B.; Martorana, D.; Moroni, G.; Gallelli, B.; Buzio, C.; et al.
Abstract : Background: Chronic periaortitis (CP) is a rare disease characterised by a fibro-inflammatory reaction that arises from the adventitia of the abdominal aorta and common iliac arteries in the retro-peritoneum.It often entrapsadjacent structures, such as ureters and the inferior vena cava. CP includes non-aneurysmal (idiopathic retroperitoneal fibrosis, IRF) and aneurysmal forms (inflammatory abdominal aortic aneurysm, IAAA) [1]. These have common clinical and histopathological features, which suggests that they represent different manifestations of the same disease. It has been reported that variants in Toll-like receptor 4 (TLR4) are associated with inflammatory diseases, and also that VEGF polymorphisms are associated with various productions and clinical expressions of VEGF in autoimmune disease [2, 3]. Objectives: To investigate whether TLR4 and VEGF polymorphisms are associated with a susceptibility to, and the clinical features of, CP or its subsets, IRF and IAAA. Methods: Using polymerase chain reaction and allele-specific oligonucleotide techniques, 102 CP patients and 200 healthy controls were genotyped for the TLR4 Asp299Gly (+896 A/G; rs4986790), for 936 C/T and 634 C/G mutations and for an 18 bp insertion/deletion (I/D) polymorphism in the VEGF promoter region polymorphisms. The patients were sub-grouped according to their type of CP (IRF/IAAA) and to the presence of established atherosclerotic disease (ischemic heart disease, cerebrovascular disease, peripheral arterial disease). Results: There was no significant difference in allele frequency or genotype of TLR4 (+896 A/G) between CP patients and controls (P=1.00). No differences in carriage rates of the alleles I, –634C and +936T of VEGF polymorphisms were found between patients with CP and healthy controls [P=0.108, OR 1.51 (95% CI 0.92–2.48) and P=0.304, OR 1.33 (95% CI 0.79–2.23), respectively].The frequency of carriage rate T of 936 VEGF polymorphism was significantly lower in patients with CP with IAAA than in those with IRF (5.3% vs 26.5%, p=0.046, OR 6.49, 95% CI 0.82–51.54). Carrying the I allele (II+ID) was significantly associated with ureteral obstruction in comparison with non-carrying patients (74% vs. 44%; P=0.006). Moreover, those patients homozygous for the inserted version (II) had a significantly increased frequency of thrombosis compared to those without (43% vs. 19.00 P=0.031). Conclusions: Our findings demonstrate that, amongst Italian patients, carrying (II +ID) polymorphism in the VEGF is associated with an increased susceptibility to the development of ureteral obstruction, and those patients homozygous for the inserted version (II) had an increased risk of thrombosis. References: Vaglio A, Pipitone N, Salvarani C. Chronic periaortitis: a large-vessel vasculitis? Curr Opin Rheumatol. 2011;23(1):1-6. Boiardi L, Casali B, Nicoli D, et al. Vascular endothelial growth factor gene polymorphisms in giant cell arteritis. J Rheumatol. 2003;30:2160-4. Boiardi L, Atzeni F, Casali B, et al. -like receptor 4 (TLR4) gene polymorphisms in Italian patients with Behçet's disease. Clin Exp Rheumatol. 2009;27(2 Suppl 53):S43-7 Disclosure of Interest: None Declared